Learning Based on Central Idea on the Topic of Electrical Circuits to Improve Students' Concept Understanding - Harjuna, Rinda; Sutopo, Sutopo; Munfaridah, Nuril (Kasuari: Physics Education Journal (KPEJ), 2024)
The unstructured pieces of students’ knowledge on electrical circuits cause students to have a diverse understanding of concepts, which will cause difficulties and misconceptions. Therefore, pieces of student knowledge that are still unstructured need to be directed into complete knowledge based on the knowledge possessed by experts through learning based on central ideas on electrical circuit topics. This research aims to improve the ability to understand concepts on electrical circuit topics through the application of central idea-based learning. The research design is one group pretest posttest. The research subjects were 145 junior high school students. The concept understanding test instrument uses the DIRECT test with 12 questions. The instrument used was valid and reliable (α = 0.7). Based on data analysis, it can be concluded that central idea-based learning is effective in increasing students' conceptual understanding as proven by the N-Gain value of 0.84 which is in the high category.